2002
DOI: 10.1029/2000jb000095
|View full text |Cite
|
Sign up to set email alerts
|

Crustal structure of the Java margin from seismic wide‐angle and multichannel reflection data

Abstract: [1] Seismic investigations across the convergent Sunda margin off Indonesia provide a detailed image of the crustal architecture of the Sunda plate boundary. The combined analysis and interpretation of wide-angle and reflection seismic data along two coincident profiles across the subduction zone are complemented by additional lines within the forearc domain, which yield some three-dimensional (3-D) constraints on the velocity-depth structure across the margin. A detailed cross section of the subduction zone i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 31 publications
(49 reference statements)
4
52
0
1
Order By: Relevance
“…Oleh sebab itu, dapat dipastikan adanya zona ekstensi di busur muka Selat Sunda. Terdapat banyak bukti adanya ekstensi dan juga struktur graben di daerah ini (Harjono et al, 1991;Gaedicke, et al, 2003, Kopp et al, 2002 sehingga sangat kecil keraguan akan adanya kelanjutan Sesar Sumatera melintasi busur muka dan berakhir di palung. Berdasarkan pergerakan lempeng dan sesar yang telah diketahui dan fitur-fitur lainnya yang diperoleh dari penelitian ini, model pergerakan tektonik disusun untuk menjelaskan kemungkinan perkembangan tektonik daerah busur muka Selat Sunda.…”
Section: Diskusiunclassified
“…Oleh sebab itu, dapat dipastikan adanya zona ekstensi di busur muka Selat Sunda. Terdapat banyak bukti adanya ekstensi dan juga struktur graben di daerah ini (Harjono et al, 1991;Gaedicke, et al, 2003, Kopp et al, 2002 sehingga sangat kecil keraguan akan adanya kelanjutan Sesar Sumatera melintasi busur muka dan berakhir di palung. Berdasarkan pergerakan lempeng dan sesar yang telah diketahui dan fitur-fitur lainnya yang diperoleh dari penelitian ini, model pergerakan tektonik disusun untuk menjelaskan kemungkinan perkembangan tektonik daerah busur muka Selat Sunda.…”
Section: Diskusiunclassified
“…Furthermore, Malod et al (1995) suggested that Cimandiri Fault Zone was extended to offshore and connected to Sumatra Fault Zone in a forearc region and formed a conjugate dextral strike-slip fault. The argument was rather weak since several offshore seimic reflection surveys indicated that more complex structures existed in the Sunda Strait forearc region (Kopp et al, 2002;Susilohadi et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The downdip limit for the Sunda Strait transect is constrained by gravity modelling with a distance of 140 km from the deformation front at a depth of 25 km (Kopp et al, 2001). Kopp et al (2002) reveal a shallow upper plate mantle in a depth of ∼22 km in the western part of Java (106/107 • E) at a distance of about 100 km from the trench from wide-angle seismic studies (landward dashed line, Figs. 3, 5).…”
Section: Off Sumatra From North To Southmentioning
confidence: 99%
“…They noted major (M w 7.0 − 7.9) earthquakes to occur off Java and the Lesser Sunda islands, whereas great thrust earthquakes were missing in that region. The main target of later studies was the deep structure of the subduction systems offshore southern Sumatra and the Sunda Strait (Kopp et al, 2001(Kopp et al, , 2003 and western Java (Kopp et al, 2002 of the Indonesian island arc.…”
Section: The Upper Platementioning
confidence: 99%